Contributions of socio-cultural approaches to “re-center” the learning processes, working with teaching in a dialogical and situational code (Praxis Educativa, 2015)
This paper develops a pedagogical reading on learning processes enrolled in educational practices, highlighting some concepts we hold in higher education research frameworks to position the centrality of learning in the constitution of subjectivities engine of human development. Theoretical tools of Sociocultural Approaches to Learning and Teaching principles enunciated as to justify reconsideration of some educational relations traditionally expressed in pedagogical discourse and conceptual pairs. They are, the relationship “theory-practice”; “Knowledge- thinking”; “Teaching and learning” terms that often take a naturalized practices enunciating character. Based on the work done research output on learning in the field of education, we consider a pedagogical task anchored in the learning process, ie generate the primary function to know, understand and manage the possibilities of appropriation of learners, refocusing the educational reason internalization, in political commitment to putting learning into teaching.
Keywords: educational research; learning; subjectivity; sociocultural approach; pedagogycal reading